Dielectric Micro‐ and Sub‐Micrometric Spacers for High‐Temperature Energy Converters. Issue 1 (13th November 2020) - Bellucci, Alessandro; Sabbatella, Gianfranco; Girolami, Marco; Mastellone, Matteo; Serpente, Valerio; Mezzi, Alessio; Kaciulis, Saulius; Paci, Barbara; Generosi, Amanda; Polini, Riccardo; Vitulano, Aniello; Vivaldi, Ilaria; et al.
Abstract : Dielectric microspacers (DMS) are important components in thermal energy converters. Engineered DMS are fabricated and characterized on different substrates by depositing patterned ceramic thin films of alumina (Al2 O3 ) and zirconia (ZrO2 ) with a thickness ranging from 0.3 to 3 μm. Both Al2 O3 and ZrO2 films are electrically and thermally optimized, finding zirconia more suitable as a thermal and electrical insulating material at high temperature, whereas the developed DMS are morphologically analyzed by scanning electron microscopy. The analysis of thermal simulations carried out with COMSOL Multiphysics allows identifying the best geometrical constraints for each single structure, whereas simulations carried out by the Fluent software allow identifying the best arrangement for DMS, leading to a solution with optimized pattern in terms of amount and spatial distribution so to achieve the required electrical and thermal insulation for practical applications. DMS are integrated within thermionic‐photovoltaic devices to be validated experimentally, and enhanced electron emission measurements are successfully performed at a cathode temperature up to 1350 °C to verify the operational feasibility and potential of this technology. Abstract : Dielectric microspacers are developed with RF reactive sputtering and a photolithographic technique for ensuring electrical and thermal insulation between the electrodes of high‐temperature energy converters. Nanostructured amorphous zirconia films are patterned according to a specific arrangement onto different substrates, and their working operations are demonstrated up to 1350 °C in hybrid thermionic‐photovoltaic devices.